Thyroid autoimmunity in relation to islet autoantibodies and HLA-DQ genotype in newly diagnosed type 1 diabetes in children and adolescents - Jonsdottir, B.; Andersson, C.; Carlsson, A.; Delli, A.; Forsander, G.; Ludvigsson, J.; Marcus, C.; Samuelsson, U.; Örtqvist, E.; Lernmark, Å.; Ivarsson, S.-A.; Larsson, H. Elding (Diabetologia, 2013)
Aims/hypothesis The aim of this work was to investigate, in children newly diagnosed with type 1 diabetes: (1) the prevalence of autoantibodies against thyroid peroxidase (TPOAb) and thyroglobulin (TGAb); and (2) the association between TPOAb, TGAb or both, with either islet autoantibodies or HLA-DQ genes. Methods Blood samples from 2,433 children newly diagnosed with type 1 diabetes were analysed for TPOAb and TGAb in addition to autoantibodies against arginine zinc transporter 8 (ZnT8RA), tryptophan zinc transporter 8 (ZnT8WA), glutamine zinc transporter 8 (ZnT8QA), glutamic acid decarboxylase (GADA), insulin (IAA), insulinoma-associated protein-2 (IA-2A), HLA-DQA-B1 genotypes, thyroid-stimulating hormone (TSH) and free thyroxine (T4). Results At type 1 diabetes diagnosis, 12% of the children had thyroid autoantibodies (60% were girls; p < 0.0001). GADA was positively associated with TPOAb ( p < 0.001) and with TGAb ( p < 0.001). In addition, ZnT8A was associated with both TPOAb ( p = 0.039) and TGAb ( p = 0.015). DQB1*05:01 in any genotype was negatively associated with TPOAb (OR 0.55, 95% CI 0.37, 0.83, p value corrected for multiple comparisons ( p c ) = 0.012) and possibly with TGAb (OR 0.55, 95% CI 0.35, 0.87, p c = 0.07). Thyroid autoimmunity in children newly diagnosed with type 1 diabetes was rarely (0.45%) associated with onset of clinical thyroid disease based on TSH and free T4. Conclusions/interpretation GADA and ZnT8A increased the risk for thyroid autoimmunity at the time of clinical diagnosis of type 1 diabetes, while HLA-DQB1*05:01 reduced the risk. However, the associations between thyroid autoimmunity and HLA-DQ genotype were weak and did not fully explain the co-occurrence of islet and thyroid autoimmunity.